2020
DOI: 10.1017/s0033291720004638
|View full text |Cite
|
Sign up to set email alerts
|

Associations between inattention and impulsivity ADHD symptoms and disordered eating risk in a community sample of young adults

Abstract: Background Symptoms of attention deficit hyperactivity disorder (ADHD) and trait impulsivity have been associated with disordered eating but are seldom assessed in community studies, or longitudinally and little is known about the mediating mechanisms. Methods We tested associations between ADHD symptoms and disordered eating cross-sectionally and between trait impulsivity and disordered eating longitudinally. We utilised data from a normative cohort of young adults (642 participants: 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Similarly, Seitz et al (2013) found that inattentive symptoms of ADHD explained more variance in ED symptoms than hyperactivity or impulsivity within an ADHD and BN sample. These findings could suggest that impaired attentional control is an underlying vulnerability factor for developing an ED among those with ADHD (Martin et al, 2022). This is consistent with findings in a longitudinal study, which identified that the combination of higher inattentive and hyperactive/impulsivity symptoms of ADHD in childhood increased the susceptibility to disordered eating in adolescence (Yilmaz et al, 2017).…”
Section: Attentional Controlsupporting
confidence: 89%
“…Similarly, Seitz et al (2013) found that inattentive symptoms of ADHD explained more variance in ED symptoms than hyperactivity or impulsivity within an ADHD and BN sample. These findings could suggest that impaired attentional control is an underlying vulnerability factor for developing an ED among those with ADHD (Martin et al, 2022). This is consistent with findings in a longitudinal study, which identified that the combination of higher inattentive and hyperactive/impulsivity symptoms of ADHD in childhood increased the susceptibility to disordered eating in adolescence (Yilmaz et al, 2017).…”
Section: Attentional Controlsupporting
confidence: 89%
“…Initial support to this hypothesis has been provided in a study reporting that emotion dysregulation may mediate the effects of negative affectivity on BE (Kukk and Akkermann, 2020). Further support comes from a previous review that suggested a mediational role of emotion dysregulation and negative affectivity in the ADHDaddictive-like eating relationship (El Archi et al, 2020), and from a previous study highlighting the mediational role of mood and feelings in the association between inattention symptoms of ADHD and risk of disordered eating (Martin et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, Seitz et al [ 49 ] found that inattentive symptoms of ADHD explained more variance in ED symptoms than hyperactivity or impulsivity within an ADHD and BN sample. These findings could suggest that impaired attentional control is an underlying vulnerability factor for developing an ED among those with ADHD [ 100 ]. This is consistent with findings in a longitudinal study, which identified that the combination of higher inattentive and hyperactive/impulsivity symptoms of ADHD in childhood increased the susceptibility to disordered eating in adolescence [ 101 ].…”
Section: Discussionmentioning
confidence: 99%